(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To estimate lipid profile in pre-eclampsia cases in Mymensingh Medical College Hospital. Materials and Methods: This cross sectional study was carried out in the dept. of Obstetrics and Gynaecology of Mymensingh Medical College and Hospital (MMCH) and outdoor Pathology Dept. of MMCH. A total 100 pregnant women were included in this study, out of which 50 were pre-eclampsia and 50 normal pregnant women. Purposive sampling technique was followed for selection of study population. Estimation of serum total cholesterol, triglyceride (TG), high density lipoprotein (HDL), low density lipoprotein (LDL) were done by colorometric method. Result: Findings of the study showed that woman with pre-eclampsia exhibits 14% higher mean plasma level of total cholesterol. It was (229.12 ± 49.31 mg/dl) in pre-eclampsia and (196.68 ± 38.60 ml/dl) in control group and the deference was statistically highly significant (p<.001). Mean plasma level of triglyceride (TG) was approximately 20% higher in the study group (251.28 ± 80.51) as compared with control (200.84 ± 80.51) which was also statistically significant (p<0.01). There was significant raised level of LDL cholesterol in pre-eclampsia (142.12 ± 44.57 mg/dl) as compared to (114.21 ± 37.81 mg/dl) in control which was statistically significant (p=0.004). HDL cholesterol level was found 13% lower in pre-eclampsia pregnant women than control group. There was statistically significant decrease of HDL cholesterol (p<0.05) in study group in which it was 36.74 ± 8.42 mg/dl and in normal pregnancy it was 42.40 ± 9.91 mg/dl. Conclusion: It can be concluded that altered serum lipid levels are seen in pre-eclampsia compared to normal pregnancy. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(2) : 61-65